Classifying and communicating risks in prediabetes according to fasting glucose and/or glycated hemoglobin: PREDAPS cohort study - Enrique Regidor; Lucía Cea-Soriano; Antonio Ruiz; Albert Goday; David Carabantes; Javier Díez-Espino; Sara Artola; Josep Franch-Nadal; for the PREDAPS Study Group (Taylor & Francis Group, 2021)
Objective Information about prognostic outcomes can be of great help for people with prediabetes and for physicians in the face of scientific controversy about the cutoff point for defining prediabetes. We aimed to estimate different prognostic outcomes in people with prediabetes. Design Prospective cohort of subjects with prediabetes according to American Diabetes Association guidelines. Main Outcome measures The probabilities of diabetes onset versus non-onset, the odds against diabetes onset, and the probability of reverting to normoglycemia according to different prediabetes categories were calculated. Results The odds against diabetes onset ranged from 29:1 in individuals with isolated FPG of 100-109 mg/dL to 1:1 in individuals with FPG 110-125 mg/dL plus HbA1c 6.0-6.4%. The probability of reversion to normoglycemia was 31.2% (95% CI 24.0-39.6) in those with isolated FPG 100-109 mg/dL and 6.2% (95% CI 1.4-10.0) in those with FPG 110-125 mg/dL plus HbA1c 6.0-6.4%. Of every 100 participants in the first group, 97 did not develop diabetes and 31 reverted to normoglycemia, while in the second group those figures were 52 and 6. Conclusions Using odds of probabilities and absolute numbers might be useful for people with prediabetes and physicians to share decisions on potential interventions.Key points Communicating knowledge on the course of the disease to make clinical decisions is not always done appropriately. Prediabetes is an example where risk communication is important because the prognosis of subjects with prediabetes is very heterogeneous. Depending on fasting plasma glucose and HbA1c levels, the odds of probabilities against diabetes onset ranged from 29: 1 to 1: 1. Depending on fasting plasma glucose and HbA1c levels, the number of subjects in 100 who revert to normoglycemia ranged from 31 to 6. Using probabilities and number absolutes on the prognosis of prediabetes may be useful for people with prediabetes and physicians to share decisions on potential interventions.